2022
DOI: 10.1002/jcla.24666
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of hsa_circ_0004812 promotes COVID‐19 cytokine storm via hsa‐miR‐1287‐5p/IL6R, RIG‐I axis

Abstract: Background SARS‐CoV‐2 is one of the most contagious viruses in the Coronaviridae (CoV) family, which has become a pandemic. The aim of this study is to understand more about the role of hsa_circ_0004812 in the SARS‐CoV‐2 related cytokine storm and its associated molecular mechanisms. Materials and Methods cDNA synthesis was performed after total RNA was extracted from the peripheral blood mononuclear cells (PBMC) of 46 patients with symptomatic COVID‐19, 46 patients with asymptomatic COVID‐19, and 46 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Following the frst exposure of SARS-CoV-2 to the host immune system, several receptors including toll-like receptors (TLRs) and NOD-like receptors (NLRs), retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs), and cyclic GMP-AMP synthase (cGAS) detect the viral particles. Afterwards, signaling cascades result in activation of innate immune responses and secretion of multiple chemokines and cytokines [6][7][8]. Some studies have shown increased levels of diferent cytokines and chemokines such as tumor necrosis factor a (TNF-α), interleukin 6 (IL-6), interleukin 7 (IL-7), C-X-C motif chemokine ligand 10 (CXCL10), C-C motif chemokine ligand 2 (CCL2), C-C motif chemokine ligand 3 (CCL3), and α-chain of IL-2 receptor [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Following the frst exposure of SARS-CoV-2 to the host immune system, several receptors including toll-like receptors (TLRs) and NOD-like receptors (NLRs), retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs), and cyclic GMP-AMP synthase (cGAS) detect the viral particles. Afterwards, signaling cascades result in activation of innate immune responses and secretion of multiple chemokines and cytokines [6][7][8]. Some studies have shown increased levels of diferent cytokines and chemokines such as tumor necrosis factor a (TNF-α), interleukin 6 (IL-6), interleukin 7 (IL-7), C-X-C motif chemokine ligand 10 (CXCL10), C-C motif chemokine ligand 2 (CCL2), C-C motif chemokine ligand 3 (CCL3), and α-chain of IL-2 receptor [9,10].…”
Section: Introductionmentioning
confidence: 99%